HIDAYATUL MUTA'ALLIM AS THE MAIN FOUNDATION OF THE FORMATION OF MODERATE ISLAMIC CHARACTER FOR STUDENTS - Sinta, Dewi; Rosidi, Ahmad; Rohman, Fathor; Jali, Hasan (Nurul Jadid University, Paiton Probolinggo, East Java, 2023)
The formation of the character of moderate Islamic students was a big responsibility of the asatidz or teachers in the country in building the younger generation. This research used research methodology with a qualitative approach with the type of case study research conducted at the Al-Qodiri Islamic Boarding School, especially in Madrasah Tsanawiyah